2014
DOI: 10.1073/pnas.1317363111
|View full text |Cite
|
Sign up to set email alerts
|

An alcohol-sensing site in the calcium- and voltage-gated, large conductance potassium (BK) channel

Abstract: Ethanol alters BK (slo1) channel function leading to perturbation of physiology and behavior. Site(s) and mechanism(s) of ethanol-BK channel interaction are unknown. We demonstrate that ethanol docks onto a water-accessible site that is strategically positioned between the slo1 calcium-sensors and gate. Ethanol only accesses this site in presence of calcium, the BK channel's physiological agonist. Within the site, ethanol hydrogen-bonds with K361. Moreover, substitutions that hamper hydrogen bond formation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 38 publications
0
80
0
Order By: Relevance
“…In contrast to the nervous system, ethanol caused inhibition of BK currents in myocytes that led to cerebrovascular constriction, in which the β1 subunit played a major role (Bukiya, Liu, et al, 2009). This group recently identified K361 on BKα as a putative binding site for ethanol (Bukiya, Kuntamallappanavar, et al, 2014). Further studies will be needed to clarify the different effects of different β subunits on the BK channel’s responses to ethanol.…”
Section: Modulation Of the Bk Channel's Pharmacological Propertiesmentioning
confidence: 99%
“…In contrast to the nervous system, ethanol caused inhibition of BK currents in myocytes that led to cerebrovascular constriction, in which the β1 subunit played a major role (Bukiya, Liu, et al, 2009). This group recently identified K361 on BKα as a putative binding site for ethanol (Bukiya, Kuntamallappanavar, et al, 2014). Further studies will be needed to clarify the different effects of different β subunits on the BK channel’s responses to ethanol.…”
Section: Modulation Of the Bk Channel's Pharmacological Propertiesmentioning
confidence: 99%
“…Additionally, preclinical studies have demonstrated that chronic ethanol reduces the function and trafficking of K Ca 2 ( Kcnn ), K V 4.2 ( Kcnd2 ), and K V 7.2 ( Kcnq2 ) channels in the nucleus accumbens (NAc) and hippocampus (Hopf et al, 2010; McGuier et al, 2015; Mulholland, Spencer, Hu, Kroener, & Chandler, 2015; Padula et al, 2015; Spencer, Mulholland, & Chandler, In Press), and pharmacologically enhancing K Ca 2 and K V 7 channel function attenuated voluntary drinking in rodents (Hopf et al, 2011; Knapp, O’Malley, Datta, & Ciraulo, 2014; McGuier et al, 2015; Padula et al, 2013). Ethanol actions on voltage- and calcium-dependent K Ca 1.1 ( Kcnma1 ) channels are involved in acute ethanol tolerance, dependence, and heavy ethanol consumption (Bukiya et al, 2014; Ghezzi, Pohl, Wang, & Atkinson, 2010; Kreifeldt, Le, Treistman, Koob, & Contet, 2013; Treistman & Martin, 2009), and Kcnma1 and Kcnq5 were identified as major hub genes for the acute actions of ethanol (Wolen et al, 2012). Deletion of the gene that encodes K ir 3.3 channels ( Kcnj9 ) enhanced ethanol conditioned place preference (Tipps, Raybuck, Kozell, Lattal, & Buck, 2016) and blunted ethanol-induced excitation of dopamine neurons and increased binge-like ethanol consumption in mice in both a limited-access 2-bottle choice (LA-2BC) model (15% v/v ethanol vs. water) and with limited-access to a single bottle of 20% v/v ethanol (Herman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yuan, Leonetti, Pico, Hsiung, & MacKinnon, 2010) and “closed” (Ca 2+ i -free; Wu, Yang, Ye, & Jiang, 2010) states of the BK channel. The model of ethanol docking onto a site of discrete dimensions in the mslo1 channel (cloned from mouse brain) (Bukiya et al, 2014) explains previously described features of modulation of BK current by ethanol and related n-alkanols: 1) ethanol action’s dependence on Ca 2+ i presence (Liu, Bukiya, Kuntamallappanavar, Singh, & Dopico, 2013; Liu, Vaithianathan, Manivannan, Parrill, & Dopico, 2008) (Fig. 1) and 2) the refractoriness of slo1 channels to n-alkanols longer than heptanol (Chu & Treistman, 1997) (Fig.…”
Section: Introduction: Is the Bk Channel An Alcohol Receptor?mentioning
confidence: 60%
“…More recent studies using engineered BK channel-forming slo1 proteins (Bukiya et al, 2014) and genetic screening or mutation of the BK channel-coding gene in Caenorhabditis elegans (Slo1) (Davis, Scott, Hu, & Pierce-Shimomura, 2014; Davis et al, 2015) have buttressed the idea of an ethanol-recognition site in the BK channel-forming protein (also termed BK α subunit or slo1 channel protein) by satisfying criteria (2) and (3). While criterion (4) has yet to be met, it should be noted that the Molecular Modeling (MM) and Molecular Dynamics (MD) data from Bukiya et al (2014) were based on crystallographic data of the BK channel cytosolic tail domain (CTD) (wherein the ethanol binding site has been mapped) in both “open” (Ca 2+ i -bound; P. Yuan, Leonetti, Pico, Hsiung, & MacKinnon, 2010) and “closed” (Ca 2+ i -free; Wu, Yang, Ye, & Jiang, 2010) states of the BK channel.…”
Section: Introduction: Is the Bk Channel An Alcohol Receptor?mentioning
confidence: 99%